1997
DOI: 10.1093/emboj/16.13.4007
|View full text |Cite
|
Sign up to set email alerts
|

T-cell subset-specific expression of the IL-4 gene is regulated by a silencer element and STAT6

Abstract: During development of CD4+ T lymphocytes in the periphery, differential expression of cytokine genes, such as those of interleukin (IL)‐2 and IL‐4, occurs in distinct T‐cell subsets. IL‐4 is a cytokine produced by T‐helper 2 (Th2) cells, and the IL‐4 receptor (IL‐4R)‐mediated signaling pathway is thought to be required for commitment to the Th2 phenotype. However, the molecular basis for development of the Th subset‐specific production of IL‐4 remains unclear. We demonstrate here that the IL‐4 promoter is func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 63 publications
2
84
0
2
Order By: Relevance
“…Indeed, in previous studies (17,18), CIITA was shown to inhibit the expression of both IL-4 and Fas-L, two genes that are regulated by the transcription factor NFAT. Moreover, both CIITA and NFAT bind to the CH3 domain of CBP (32,(41)(42)(43). Although we have not identified the transcription factor(s) affected by CIITA-CBP interactions, several possibilities exist.…”
Section: Fig 5 F-ciita and F-⌬ct But Not F-⌬59 -94 Bind Cbpmentioning
confidence: 89%
“…Indeed, in previous studies (17,18), CIITA was shown to inhibit the expression of both IL-4 and Fas-L, two genes that are regulated by the transcription factor NFAT. Moreover, both CIITA and NFAT bind to the CH3 domain of CBP (32,(41)(42)(43). Although we have not identified the transcription factor(s) affected by CIITA-CBP interactions, several possibilities exist.…”
Section: Fig 5 F-ciita and F-⌬ct But Not F-⌬59 -94 Bind Cbpmentioning
confidence: 89%
“…However, IL-4 expression is controlled not only by the IL-4 promoter, but by several other regulatory elements, including enhancers, silencers, and locus control regions, which become targets of transcription factors and chromatin-remodeling factors (3,4). There are IRF-binding sites within the silencer region (35). Therefore, IRF-4 may affect not only promoter activity of the target genes, but also the chromatin environment of the target genes in regulating gene expression (36).…”
Section: Discussionmentioning
confidence: 99%
“…Mice expressing the human DTR under the control of IE element (for Mas-TRECK) and 39UTR element (for Bas-TRECK) in the Il4 gene locus were generated by a Tg strategy. The basic pIL-4 construct was made by insertion of the 59enhancer (2863 to 25448; the start codon is defined as 0) (22) and the IL-4 promoter from position 264 to 2827. The human DTR fragment was isolated from the DTR/pMS7 vector (provided by Dr. M. Tanaka, Research Center for Allergy and Immunology, the Institute of Physical and Chemical Research) and inserted into the basic pIL-4 construct.…”
Section: Micementioning
confidence: 99%